2016
DOI: 10.1159/000448481
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adolescent Dimensional Borderline Personality Pathology with Past and Current Nonsuicidal Self-Injury and Lifetime Suicidal Behavior: A Clinical Multicenter Study

Abstract: Descriptive diagnoses of nonsuicidal self-injury (NSSI) and suicide attempts (SAs) may detract from underlying dimensional borderline personality pathology (D-BPP). This study aimed to investigate D-BPP in adolescent inpatients with NSSI and SAs. A consecutive sample of 359 adolescent inpatients was assessed for current and past NSSI and life-time SAs. D-BPP and current mental health problems were measured using the Dimensional Assessment of Personality Pathology and the Strengths and Difficulties Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
0
11
1
Order By: Relevance
“…It is difficult to compare these rates to the literature that is extremely limited as most studies on adolescent suicide and self‐injury do not assess for BPD, and for the studies that do, BPD traits but not the full diagnosis of BPD are the diagnostic outcome. Data from Kaess et al who studied lifetime suicide attempts and self‐injurious episodes in hospitalized adolescents with mixed diagnoses, including BPD, revealed rates roughly 50% less than our findings; and 50% for self‐injury and 35% for suicide attempts.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…It is difficult to compare these rates to the literature that is extremely limited as most studies on adolescent suicide and self‐injury do not assess for BPD, and for the studies that do, BPD traits but not the full diagnosis of BPD are the diagnostic outcome. Data from Kaess et al who studied lifetime suicide attempts and self‐injurious episodes in hospitalized adolescents with mixed diagnoses, including BPD, revealed rates roughly 50% less than our findings; and 50% for self‐injury and 35% for suicide attempts.…”
Section: Discussioncontrasting
confidence: 79%
“…More recently, Nakar et al studied 2‐year trajectories of self‐harm, suicide attempts and substance misuse in a community sample of 513 adolescents and found all three self‐destructive behaviours were highly overlapping and significantly associated with BPD symptomatology. In a sample of adolescent inpatients across Germany, 35% had a history of a suicide attempt, and dimensional BPD psychopathology conferred additional relative risk for a lifetime suicide attempt (OR = 2.36, 95% CI 1.69–3.30, p < 0.001) . In a study comparing suicidal adolescents with and without BPD, those with BPD exhibited more suicide attempts, aggression and psychiatric co‐morbidity …”
Section: Introductionmentioning
confidence: 99%
“…For most adolescents, NSSI is a way to cope with intense emotions, self-critical thoughts, or to signal distress to others (2). NSSI is prospectively associated with increased risk for a variety of negative mental health outcomes, including anxiety, depression, disordered eating, and personality disorders (7)(8)(9)(10). For example, an earlier age of onset of NSSI (before age 13) and longer duration of NSSI during adolescence have been shown to significantly predict adult borderline personality disorder (BPD) (8).…”
Section: Introductionmentioning
confidence: 99%
“…NSSI is prospectively associated with increased risk for a variety of negative mental health outcomes, including anxiety, depression, disordered eating, and personality disorders (7)(8)(9)(10). For example, an earlier age of onset of NSSI (before age 13) and longer duration of NSSI during adolescence have been shown to significantly predict adult borderline personality disorder (BPD) (8). Also, several studies show NSSI to be a potent and unique risk factor for attempted suicide (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…In a community-dwelling study with Italian adolescents, findings showed that non-suicidal self-injury (NSSI) and emotional dysregulation are moderately related to BPD features in adolescents [ 41 ]. This finding was replicated by Kaees and colleagues [ 42 ] in adolescent inpatients with NSSI and suicide attempts (SA) and showed that dimensional borderline pathology was associated with NSSI and SA. In line with recent developmental theories explaining BPD (i.e., mentalisation-based theory), Sharp and colleagues [ 43 ] found that specifically hypermentalizing (i.e., ascribing intentions and beliefs to people where non is) mediated the relationship between attachment coherence and borderline pathology.…”
Section: Introductionmentioning
confidence: 62%